Balancing Workload And Quality Of Work Life: Key To Reducing Turnover Intentions In Startup Companies - Suryani Maryam (Jurnal Ekonomi, 2024)
Employee turnover is a critical issue for organizations, affecting productivity, morale, and operational continuity. Understanding the determinants of turnover intention is essential for developing strategies to retain valuable employees. This study investigates the factors influencing turnover intention among employees at PT ETU in Jakarta. Utilizing a saturated sampling method, data were collected from all 55 employees of the company. The analysis was conducted using path analysis techniques, with data processed through SmartPLS 4.0. The findings reveal that workload exerts a positive and significant impact on turnover intention, indicating that higher workload levels are associated with an increased likelihood of employees intending to leave the organization. Conversely, the quality of work life demonstrates a negative and significant effect on turnover intention, suggesting that better quality of work life reduces the propensity for employees to consider leaving their jobs. These results underscore the importance of managing workload and enhancing the quality of work life to mitigate turnover intention at Start-up Company.